2001
DOI: 10.1016/s0960-9822(01)00226-3
|View full text |Cite
|
Sign up to set email alerts
|

RNA-directed transcriptional gene silencing in plants can be inherited independently of the RNA trigger and requires Met1 for maintenance

Abstract: RNA-triggered events can lead to heritable changes in gene expression, and it is possible that initiation of other epigenetic phenomena such as trans-silencing and paramutation may have an RNA component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
263
2
6

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(279 citation statements)
references
References 58 publications
8
263
2
6
Order By: Relevance
“…In this case, silencing occurred at the transcriptional gene silencing (TGS) level and correlated with de novo methylation of promoter sequences [44]. Unlike the response of PTGS to dsRNA in plants, TGS is heritable [45], and evidence is only now beginning to accumulate suggesting that TGS and PTGS are biochemically related silencing pathways.…”
Section: Dsrna and Heterochromatinmentioning
confidence: 99%
“…In this case, silencing occurred at the transcriptional gene silencing (TGS) level and correlated with de novo methylation of promoter sequences [44]. Unlike the response of PTGS to dsRNA in plants, TGS is heritable [45], and evidence is only now beginning to accumulate suggesting that TGS and PTGS are biochemically related silencing pathways.…”
Section: Dsrna and Heterochromatinmentioning
confidence: 99%
“…Subsequenly, it was shown that this de novo methylation activity required formation of dsRNA and of processed siRNA [76]. siRNAs direct DNA methyltransferases (MET1, CMT3), histone methyltransferases (DDM1, Kryptonite) and histone deacetylases onto targets promoter regions and induce transcriptional gene silencing in plants [77,78]. Although not all the components of the RNAdependent DNA methylation machinery have been identified, it seems that a similar process exists in mammalian cells.…”
Section: Putative Regulatory Role Of the Rnai Pat Hways In T H E E Pimentioning
confidence: 99%
“…It is now known that when a silencing locus produces dsRNAs corresponding to transcribed sequences of a target locus, HDGS occurs by PTGS (Waterhouse et al 1998;Chuang and Meyerowitz 2000), which is similar to RNAi in animals (Fire et al 1998). In contrast, when a silencing locus produces dsRNAs corresponding to promoter sequences of the target locus, HDGS occurs by TGS (Mette et al 1999(Mette et al , 2000Jones et al 2001;Sijen et al 2001). In plants, both dsRNAinduced TGS and PTGS result in methylation of homologous sequences at the target locus.…”
Section: Introductionmentioning
confidence: 99%